2019
DOI: 10.3389/fnins.2019.00807
|View full text |Cite|
|
Sign up to set email alerts
|

Computational Methods for Resting-State EEG of Patients With Disorders of Consciousness

Abstract: Patients who survive brain injuries may develop Disorders of Consciousness (DOC) such as Coma, Vegetative State (VS) or Minimally Conscious State (MCS). Unfortunately, the rate of misdiagnosis between VS and MCS due to clinical judgment is high. Therefore, diagnostic decision support systems aiming to correct any differentiation between VS and MCS are essential for the characterization of an adequate treatment and an effective prognosis. In recent decades, there has been a growing interest in the new EEG compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Therefore, although we do find a consistent set of regions correlating with CRS-R communication subscale in the two studies, spanning left thalamus and putamen, the details of the associations between all subscales and subcortical brain pathology remain to be fully characterized. Third, consistent with prior work (Corchs et al, 2019; Estraneo et al, 2016; Lechinger et al, 2013), we find that EEG spectral features are relevant to diagnosing a patient's chronic state of consciousness (i.e. VS v. MCS), a decision known to be susceptible to a relatively high misdiagnosis rate (Monti et al, 2015; Monti & Owen, 2010; Schnakers et al, 2009; Schnakers, Giacino, Kalmar, Piret, & Lopez, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, although we do find a consistent set of regions correlating with CRS-R communication subscale in the two studies, spanning left thalamus and putamen, the details of the associations between all subscales and subcortical brain pathology remain to be fully characterized. Third, consistent with prior work (Corchs et al, 2019; Estraneo et al, 2016; Lechinger et al, 2013), we find that EEG spectral features are relevant to diagnosing a patient's chronic state of consciousness (i.e. VS v. MCS), a decision known to be susceptible to a relatively high misdiagnosis rate (Monti et al, 2015; Monti & Owen, 2010; Schnakers et al, 2009; Schnakers, Giacino, Kalmar, Piret, & Lopez, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…The output is an enormous 2-dimensional functional connectivity matrix between all channels, which is hard to interpret. However, connectivity results can be summarized with graph theory methodologies, to quantify the changes in the connectivity of a network 31 . It has been suggested that a neuronal network needs an optimal balance between integration and segregation to function fully and share information effectively between brain regions 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we provide an overview of the research over the last 20 years (2000-2020) of all the different parameters extracted from EEG recordings used for diagnosis and prognosis, and we summarize our findings in two tables at the end. Some existing reviews just focus on prognosis [24] or just present work conducted on resting-state EEG [25], [26]. Other reviews focus on BCI [27] or also EEG reactivity and transcranial magnetic stimulation (TMS)-EEG [28,29].…”
Section: Introductionmentioning
confidence: 99%